The Making of a Dream - Laura Wides-Munoz (Harper, 2018)
The Making of a Dream begins at the turn of the millennium, with the first of a series of "Dream Act" proposals; follows the efforts of policy makers, activists, and undocumented immigrants themselves, and concludes with the 2016 presidential election and the first months of the Trump presidency. The immigrants’ coming of age stories intersect with the watershed political and economic events of the last two decades: 9/11, the recession, the wars in Iraq and Afghanistan, the Obama presidency, and the rebirth of the anti-immigrant right.